Pengembangan Perencanaan Pendidikan Islam (Konsep Strategi Pengembangan Di Indonesia) - Dwi Priyanto (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Planning is a very important and strategic factor of its nature as a guide for the implementation of an activity in order to achieve the desired goals or objectives. Planning process as a series of activities is undertook to prepare a decision on what is expected to occur and what will be done. In the field of Islamic education, planning is one key factor for the effectiveness of the implementation of educational activities, national and local level. But in practice of the Islamic education implementation, educational planning is viewed as complementary factors, so objectives are not achieved maximally. The importance of planning development strategies of Islamic education in Indonesia is due to the implementation of Islamic education in Indonesia still needs to be done a repositioning effort, so that Islamic education can truly achieve its goals. Keywords: Strategy development and Islamic educational planning.